Design of dissolution media for in-vitro bioequivalence testing of Lamivudine - Nagiat T Hwisa, Shanta Kumari Adiki, Prakash Katakam, Babu Rao Chandu (Journal of Applied Pharmaceutical Science, 2013)
The present investigation is aimed at developing the stability indicating dissolution media for the determination of lamivudine (3TC) in pharmaceutical dosage forms. The stability of 3TC was tested in various dissolution media maintained at ambient temperature and 37 oC for 48 hrs. Stability studies of 3TC in various media indicated that the drug was stable in 0.1M HCl, pH 1.2 KCl-HCl buffer, pH 6.2 and pH 7.0 phosphate buffers. The λmax were found to be 280.0, 278.8, 273.0 and 271.5nm for 0.1M HCl, pH 1.2 KCl-HCl buffer, pH 6.2 and pH 7.0 phosphate buffers respectively with low CV of
Keywords: Lamivudine, Stability indicating, Bioequivalence stu